Electrospinning of PVDF nanofibers incorporated cellulose nanocrystals with improved properties - Aydemir, Deniz; Sozen, Eser; Borazan, Ismail; Gunduz, Gokhan; Ceylan, Esra; Gulsoy, Sezgin Koray; Bardak, Timucin (Springer, 2023)
Polyvinylidene fluoride (PVDF) nanofibers with cellulose nanocrystals (CNCs) were produced with the electrospinning technique at the CNC loading rates of 0.25, 0.50, 0.75, and 1 wt%. CNCs were obtained with acid hydrolysis of microcrystalline cellulose with 64 wt% sulfuric acid. The material properties of CNCs have been studied with scanning electron microscopy (SEM), transmission electron microscopy, atomic force microscopy, X-ray diffraction (XRD), thermal analysis (TGA), ultraviolet (UV-Vis) spectroscopy, and fourier transform infrared spectroscopy. The PVDF nanofibers with CNCs were produced by the electrospinning technique. The material characterization of neat PVDF and the PVDF-CNC nanofibers were investigated with XRD, TGA, FT-IR, and morphological properties with SEM. The morphological results showed that CNCs were observed as needle-shaped rods and lengths for CNCs were generally in the range of 25-50 nm and 150-300 nm. The crystallinity and crystal size of CNCs were calculated as 75% and 4.8 nm, respectively. CNCs showed the decomposition stages at 100-250 degrees C and 300-375 degrees C for the evaporation of the water and decomposition reactions of cellulose, respectively. CNCs exhibited a weak absorbance at 265 nm according to the UV-Vis. As seen in the results of the nanofibers, it was found that CNCs generally decreased the diameters of the nanofibers obtained with the electrospinning when the loading rates of CNCs were raised. The presence of CNCs generally improved the thermal stability of the nanofibers. XRD results showed that crystallinity generally increased with adding CNCs. In FT-IR spectra, any difference was not detected among the PVDF-CNC nanofiber spectra.
Keywords: Electrospun nanofibers; Renewable nanomaterials; Polyvinylidene fluoride (PVDF); Cellulose nanocrystals